Dissolved organic matter characterisation and temporal trends in Terra Nova Bay (Ross Sea, Antarctica) - MISIC, CRISTINA; CASTELLANO, MICHELA; RUGGIERI N; POVERO, PAOLO (Estuarine, Coastal and Shelf Science, 2006)
In Terra Nova Bay, a coastal area of the Ross Sea (Antarctica), the dissolved organic matter (DOM) (proteinlike and humiclike) in the seawater from two sampling stations was studied using the synchronous fluorescence technique and the evaluation of the dissolved proteins during the ice-free time lag (approximately four weeks). Moreover, a simple experiment was carried out to assess the DOM consumption by bacteria. At the two sampling stations, we observed changes in the concentrations of the different DOM types over time, related to the phytoplanktonic development (up to 5 mg l-1 of chlorophyll-a) and decrease (below 2 mg l-1 of chlorophyll-a within 10 days). A significant correlation was observed between the chlorophyll-a and the DOM. The proteinlike signal ranged from maximum values higher than 5 mg l-1 at the beginning of the sampling period to values lower than 2 mg l-1 at the end. Similarly, the humiclike compounds ranged from the highest values at the beginning (more than 30 mg l-1) to values lower than 20 mg l-1 at the end of the sampling time. The dissolved proteins also showed notable changes over time, showing the highest values (more than 0.4 mg l-1) during the first days of the sampling period and reduced concentrations (variable, but also below 0.05 mg l-1) at the end. Due to the stability of the water column and of the meteorological conditions, we propose major roles for photodestruction and bacterial consumption in the potential ‘‘disappearance’’ of the DOM. The surface layer photodestruction (calculated extrapolating the rates from previous literature data) might explain the disappearance of 7% of the fluorescent DOM, leaving the predominant role to bacterial consumption. The experimental data confirmed the potential ability of bacteria to transform and/or take up the fluorescent DOM and the dissolved proteins. These results suggest that only a small part of the DOM is available for export during the winter mixing, reducing the role of the coastal Antarctic area in the CO2 sink.